Worldwide survey on the current practice of asymptomatic urinary stone management: a survey from eau, young academic urologists (yau), endourology and urolithiasis working party - TANIDIR, YILÖREN (My University, 2022)
INTRODUCTION AND OBJECTIVE: Management of asymptomatic kidney stones is a topic of ongoing debate with follow-up and treatment guidelines based on low-level evidence. Our aim was to evaluate current management of asymptomatic urinary stones. METHODS: A 70-question survey was designed in collaboration with EAU, Young Academic Urologists (YAU), Section of Uro-Technology (ESUT) and Section of Urolithiasis (EULIS) groups and distributed. Responders filled out several clinical scenarios either as counselling urologists, or as patients themselves. RESULTS: A total of 212 (30.2%) responses were obtained. Median responder age was 39 years. Demographic information is given in Table 1. 159 (75%) responders were interested in “urolithiasis”. 175 (82.5%) had never experienced a renal colic and 89.6% had never undergone any kind of urolithiasis treatment.Overall, urologists as patients themselves opted significantly more frequently for a conservative approach (29% vs. 25%) or SWL (17% vs. 14%), and significantly less frequently for a URS (35% vs. 39%) or PCNL (19% vs 23%), compared to what urologists would recommend to their patients (p <0.001) (Figure 1A).Of all demographic parameters, having had a renal colic was an independent predictor of an interventional approach (OR 1.5, 95% CI 1.1-2.0; p[0.01), whereas having had an intervention was an independent predictor of a conservative approach (OR 1.01, 95% CI 1.01-1.19; p[0.04). Overall, no significant differences in follow-up schedules were found between urologists and urologists as patients themselves (Figure 1B and 1C). Only 19% of all kidney stones were adjourned for follow-up within 3 months, compared to 89% for ureteral stones (p<0.001). CONCLUSIONS: Current treatment and follow-up patterns of asymptomatic urinary stones are in agreement with international guidelines on symptomatic stones. Urologists tend to choose the lesser invasive treatment option as a patient themselves, compared to what they choose for their patients.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Üroloji; Medicine; Health Sciences; Surgery Medicine Sciences; Urology; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; Nefroloji; Cerrahi; Nephrology; Surgery